Women, Priesthood, and Catholic Celibacy: An Empirical Approach in Latin America. - Domínguez, Alejandro Díaz (Journal of Feminist Studies in Religion (Indiana University Press))
The Catholic Church has historically reserved access to the priesthood for celibate men, excluding married individuals and women. The 2019 Pan-Amazon Synod sought to address this issue. Drawing on theological reviews and literature on religious competition, this article analyzes surveys conducted across 18 Latin American countries plus the US territory of Puerto Rico to explore the extent to which religious denomination (Catholic and Protestant/evangelical churches), religious dimensions (believing, behaving, moral values, alternative, and charismatic), and country-level measures (Catholics per priest and the effective number of religions) are associated with attitudes toward access to the priesthood. Multilevel logistic models were used to reveal that religious affiliation, religious attitudes, and contextual measures (such as the shortage of Catholic priests) are related to lack of support for married priests. However, only religious attitudes are associated with attitudes toward women's access to the priesthood, specifically the charismatic dimension.